Enhancement strategies for efficient activation of persulfate by heterogeneous cobalt-containing catalysts: A review. (March 2022) - Li, Bo; Wang, Yun-Fei; Zhang, Lu; Xu, Huan-Yan
Abstract: As a clean and efficient technology for the degradation of organic contaminants, sulfate radical based advanced oxidation processes (SR-AOPs) have attracted more and more attention in the past decades. Cobalt is regarded as the most reactive and efficient non-noble metal catalyst for the activation of persulfate including peroxymonosulfate (PMS) and peroxydisulfate (PDS) to produce sulfate radicals. Due to the limitations of homogeneous catalytic systems, the heterogeneous cobalt-containing catalysts have been emerged and rapidly developed. Various strategies have been schemed to further enhance the activation ability of persulfate by heterogeneous cobalt-containing catalysts. This paper provides an overview on the recent progress in enhancement strategies for the highly efficient activation of persulfate by heterogeneous cobalt-containing catalysts. With a brief introduction on the chemistry and feature of sulfate radical reactions catalyzed by homogeneous Co 2+ /Co 3+ species, the main strategies for enhancing persulfate activation by heterogeneous cobalt-containing catalysts are summarized, such as surface and morphology design, multiple reactive centers design, organic-inorganic hybrids and heterostructure composites. Future perspectives of heterogeneous SR-AOPs systems catalyzed by cobalt-containing catalysts are outlined. Graphical abstract: Image 1 Highlights: Enhancement strategies for persulfate activation are generalized and summarized. The potential mechanisms of heterogenous cobalt-containing catalysts are discussed. A future blueprint for the heterogeneous cobalt-containing catalysts is described.